En vendsysselsk Jernaldergrav - Friis, Palle (Kuml, 1961)
An I ran Age Grave from Vendsyssel. In 1960, the Vendsyssel Museum of History investigated al the farm of Sdr. Stokholm, north of Sindal in Vendsyssel, a stone-built grave from the Roman Iron Age, of a type typical of Vendsyssel 1). Its size, contents and state of preservation justify description. After removal of the top-soil from a large area, two oval, 3 m long, dark patches were observed in the sand, lying east-west, 1 ½ m apart. Two graves were found, that to the south having been almost completely destroyed, whereas the northern grave was intact, in spite of the covering of soil being only 10 cm thick (fig. 1). A stone slab, nearly 2 X 5 m long, covered the chamber, the interstices between capstone and supporting stone being packed with small stones, fitting so closely that the top 50 cm of the burial chamber was free of earth. The chamber, which was built of three courses of stone, was 1 ½ m deep and: nearly rectangular at the bottom course, measuring 1.85 X 1.15 m. The two upper courses were corbelled in as a false vault to fit the capstone in the top course 2). The floor of the grave was flat and covered with a millimeter-thick layer of black, greasy earth. All traces of the body had disappeared but the disposition of the burial offerings indicates the approximate position (fig. 2). In the middle of the southern half of the grave lay the head of a small pin of spirally twisted silver wire (no. 1 in fig. 2). Between this and the south-west corner a 5 cm long, ribbon-fibula with transverse ridge was found (no. 3 in fig. 2 and fig. 3). The foot of the clasp is decorated with a serrated line along both edges and under the ridge with two circles. The ridge itself is undecorated but the groove on its crest presumably carried a twisted gold wire originally. The ridge is bounded by beading along both sides. The top half of the clasp is slightly arched and ornamented with three strips of beading. The pin and spiral, which has 12 turns, are also of silver. 15 cm from the east end of the grave lay the head of another pin, this time of silverplated bronze (no. 2 in fig. 2). The bottom of an earthenware vessel filled with small stones stood in the south-west corner and the rest of the burial furniture, consisting of two single-edged iron knives (nos. 4-5 in fig. 2) and a complete set of six food-vessels (three bowls, two large vases, a pedestalled beaker and a cup) had been placed in the northern half. Judging from the position of pins and pottery, the body must have lain in the southern half, facing north. This is diametrically opposed to normal practice, where the body lies in the northern half, with the head in the west, facing south. All the pots exemplify the fine craftsmanship that distinguishes the pottery of the Roman Iron Age in Vendsyssel. The equine head in relief on the bowl illustrated in figs. 4-5 (no. 11 in fig. 2) is quite unique among Danish material. The head is 4.2 cm high and has long ears, large eye-sockets and a muzzle with pricked nostrils. This decoration in relief places the vessel among the Vendsyssel pots with heads in relief, of which four have human faces. There are also several with carefully modelled birds 5). The bowl has a black, burnished surface and is decorated with double-lined hatched bands containing a rhombic pattern and beneath these double-lined hatched pendent curves. The rim is facetted and the bottom concave. The height of the bowl is 7.5 cm. The large embossed vase (no. 13 in fig. 2 and fig. 6) is also unique in Vendsyssel. It has a black, burnished surface and a strongly splayed rim, decorated on top with three broad furrows. The shoulder carries a facetted, x-shaped lug and three large, round bosses, pressed out from the inside of the vase. These are surrounded by a 12 mm broad band with impressed rosettes. Below the bosses is a three-lined ribbon in a kind of degenerated meander. This kind of vessel has not previously been found north of Randers Fjord, but a group of vases with this ornamentation is found on the east coast of Jutland 6). Here the bosses are surrounded by a band, but without the rosettes. These seem to represent rivets and if this be the case the bosses should be interpreted as shield bosses. The rest of the pottery is more typically Vendsyssel and is mostly burnished with facetted rim. In the south-east corner stood the bottom half of a reddish-yellow pot filled with small stones of varying shape and colour (no. 6 in fig. 2 and fig. 7). Small stones are not unknown in Vendsyssel graves. Often they lie directly on the ground, sometimes on a broken piece of pottery, but seldom in an entire pot. They have been interpreted as the pieces in a game, but as the number varies greatly from grave to grave, and shape and size also vary, this hardly seems feasible. An alternative theory considers the stones to be a symbol for food, e. g. eggs and loaves 7). Then one merely wonders why they are nearly always placed on broken pottery or the ground itself, at the side of so many fine food-vessels. Most of the pottery and the grave itself are characteristic of the Early Roman Iron Age in Vendsyssel and the fibula links the find to the same period on the Continent 8). Palle Friis.